DAMPAK KERJASAMA MULTILATERAL TERHADAP PERDAGANGAN PRODUK PERTANIAN - Dedi Budiman Hakim (School of Business, Bogor Agricultural University (SB-IPB), 2005)
Multilateral trade agreement under the auspice of the GATT/WTO is expected to change the nation’s competitiveness in the global economy. In the context of the agricultural agreement, there are three mayor changing policies to be committed by the WTO members: (a) market access, (b) export subsidies and (c) domestic support. Likewise, ASEAN regional agreement (AFTA) will reduce the relative price of international prices to the domestic prices and the exploitation of the comparative advantage. The questions to be answered is whether such multilateral agreements affect agricultural trade in the region. A recursive-dynamic computable general equilibrium (CGE) and the Global Trade Analysis Project (GTAP) database were used to assess such impacts. Two important scenarios were then considered: APEC and AFTA scenarios. The results indicate that as import tariff levels are completely removed, the demand for imported goods would certainly be increased. This is because domestic consumers (private consumers and industries) would face decreasing domestic prices. However, the size of import changes depends on the initial tariff rates. The higher the initial intra-regional tariffs, and the larger the tariff cuts, the higher the gains from the trade creation. Under the AFTA trade liberalisation, rice output in the ASEAN member countries with the exception of Thailand is projected to shrink. The AFTA tariff reduction would cause an increase in exports in most ASEAN economic sectors. Focusing on the export changes in the agricultural sectors, it is reported that the cereal and processed milk sectors are predicted to have noticeable increases in their exports. However, since trade liberalisation would have adverse effects on the uncompetitive producing sectors, adjustment assistance is highly recommended in order to compensate for any losses; for instance, reduced farm incomes.